Um estudo Histórico sobre o Parajiu-jitsu - Oliveira Gonçalves, Luis Carlos; Anibal Monteiro de Magalhães Neto (South American Journal of Basic Education, Technical and Technological, 2021)
The present work is the result of a study that proposed to present the historical process of Parajiu-jitsu. Conventional jiu-jitsu is linked to competition, and there were no parameters for the insertion of practitioners with disabilities. The para-athletes went to the competitions to compete and broadcast a message, but were often prevented from fighting for the organizers. Parajiu-jitsu is adapted according to the functional classification of each athlete. The new modality presents itself not only as a method of physical gain, but also as a tool for rehabilitation, social formation and integration, indicating its public health aspects. Policies to increase participation in school sports can be justified as part of public health strategies to promote mental and physical health.